A Review Of The Literature On Sensor-Based Dynamic Balance Tools For Postural Stability Control - Komaini, Anton; Rifki, Muhamad Sazeli; Welis, Wilda; Handayani, Sri Gusti; Alimuddin, Alimuddin; Pranoto, Nuridin Widya (STAMINA, 2025)
Equilibrium is the capacity to hold a position within the bounds of support or stability. It is demonstrated that the posture control system is crucial for preserving balance on a small support base. The intricate process makes it challenging to evaluate balancing capacities succinctly and completely. By examining numerous studies that evaluate postural balance using a variety of mechanical tools and offering a thorough summary of popular mechanical tools for this purpose, this study expands on earlier research. Finding the appropriate activity and equipment to regulate postural stability is the aim of this review. We used VOSviewer, a tool for analyzing bibliometrics from the Scopus database from Elsevier and Google Scholar, to conduct an electronic search across several prestigious journals. 154 relevant items were found after a literature search. A more thorough analysis reveals that the chosen literature solely discusses mechanical instruments for assessing static and dynamic balance. Only 12 articles from the evaluation satisfied the requirements. Four publications inertial balance sensors, Biodex Balance Systems, force plates, and 3D Joint Kinematic sensors are directly related to sensor-based dynamic tools for postural stability control, according to the search results. This sensor-based dynamic balance tool is a useful tool for teaching and assessing postural stability in a variety of contexts, including medical rehabilitation.